Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.jctc.0c00021
|View full text |Cite
|
Sign up to set email alerts
|

Computing Surface Acidity Constants of Proton Hopping Groups from Density Functional Theory-Based Molecular Dynamics: Application to the SnO2(110)/H2O Interface

Abstract: Proton transfer at metal oxide/water interfaces plays an important role in electrochemistry, geochemistry and environmental science. The key thermodynamic quantity to characterize this process is the surface acidity constant. An ab initio method that combines density functional theory based molecular dynamics (DFTMD) and free energy perturbation theory has been established for computing surface acidity constants. However, it involves a reversible proton insertion procedure in which frequent proton hopping, e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Interestingly, hematite (0001) surface is similar to alumina (0001) and the predicted pK a of Fe 2 OH by AIMD is 21.7, comparable with Al 2 OH, but much higher than the value predicted by the valence bond model (about 12) 142 . The pK a of SnO 2 is consistent with experimental PZC measurements 143 . Understanding disagreements between simulations and experimental measurements is crucial to model the interface in acidic or basic solutions because the surface protonation state, surface charge density, and interfacial water orientation are mainly determined by the surface pK a .…”
Section: Water/alumina (Aluminum Oxide) Interfacessupporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly, hematite (0001) surface is similar to alumina (0001) and the predicted pK a of Fe 2 OH by AIMD is 21.7, comparable with Al 2 OH, but much higher than the value predicted by the valence bond model (about 12) 142 . The pK a of SnO 2 is consistent with experimental PZC measurements 143 . Understanding disagreements between simulations and experimental measurements is crucial to model the interface in acidic or basic solutions because the surface protonation state, surface charge density, and interfacial water orientation are mainly determined by the surface pK a .…”
Section: Water/alumina (Aluminum Oxide) Interfacessupporting
confidence: 75%
“…142 The pK a of SnO 2 is consistent with experimental PZC measurements. 143 Understanding disagreements between simulations and experimental measurements is crucial to model the interface in acidic or basic solutions because the surface protonation state, surface charge density, and interfacial water orientation are mainly determined by the surface pK a .…”
Section: Copyright (2019) American Chemical Societymentioning
confidence: 99%
“…In the first work of applying finite-field DFTMD for modeling EDLs, 23 it was found that the Helmholtz capacitance at electrified rutile TiO 2 (110)/NaCl interfaces is much higher at high pH than that at low pH for the given surface charge density, and the interfacial proton transfer at low pH increases significantly the capacitance value. Compared with rutile TiO 2 , the isostructural cassiterite SnO 2 has a characteristic dissociative water adsorption, 26 , 27 which involves terminal adsorbed water Sn 5c O w H 2 to bridge oxygen site Sn 2 O br as …”
mentioning
confidence: 99%
“…Subsequently, finite-field DFTMD has also been applied to study SnO 2 , which is an isostructure of TiO 2 and has a characteristic dissociative water adsorption 57 . Jia et al 53 computed the Helmholtz capacitance of the SnO 2 (110)/NaCl electrolyte interface and developed a differential Helmholtz capacitance model accordingly.…”
Section: Atomistic Modelling Of the Protonic Double Layermentioning
confidence: 99%